Analisis Konsentrasi Spasial dan Strategi Pengembangan Industri Kecil di Jawa Timur - Nurul Ma'rifatus Sa'diyah; Siti Komariyah; Anifatul Hanim (e-Journal Ekonomi Bisnis dan Akuntansi, 2017)
This study aims to determine the location of the concentration of industry in East Java and determines the development strategyof small industry in East Java. In this study using quantitative descriptive analysis tools and Analytical Hierarchy Process(AHP). Based on the results of this research is that the location of concentration of small industries in East Java, contained infour district/city namely: Tulungagung, Malang, Blitar and Bondowoso. In the determination of strategy of development ofsmall industries in order of priority to consider the overall criteria (training, financing, partnerships, technology) weconcluded the first priority of increased promotion, differentiation of products, improving the quality of human resources andthe expansion of the market.